2013
DOI: 10.1378/chest.12-0212
|View full text |Cite
|
Sign up to set email alerts
|

Training for Linear Endobronchial Ultrasound Among US Pulmonary/Critical Care Fellowships

Abstract: CHEST / 143 / 2 / FEBRUARY 2013 423 P ulmonary and critical care medicine has seen vast improvements in technology develop over the past decade. Endobronchial ultrasound (EBUS) is one such technology that has revolutionized the bronchoscopist's ability to both visualize and sample structures surrounding the tracheobronchial tree. Over the past 10 years, there has been a growing body of medical literature. A PubMed search for publications including EBUS from January 2002 cited 479 references, with more than one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 34 publications
0
28
0
1
Order By: Relevance
“…A recent survey among pulmonary fellowship directors in the USA found that only 30% of programs had a formal protocol in place to evaluate EBUS competency [14]. We argue that high-fidelity VR simulators like the EBUS simulator used in this study could be used for initial training and assessment of basic competence before proceeding to supervised practice on patients.…”
Section: Discussionmentioning
confidence: 96%
“…A recent survey among pulmonary fellowship directors in the USA found that only 30% of programs had a formal protocol in place to evaluate EBUS competency [14]. We argue that high-fidelity VR simulators like the EBUS simulator used in this study could be used for initial training and assessment of basic competence before proceeding to supervised practice on patients.…”
Section: Discussionmentioning
confidence: 96%
“…Endobronchial ultrasonography (EBUS) and transoesophageal ultrasonography (EUS) have replaced surgical mediastinoscopy as the first choice to obtain tissue confirmation [1,2]. Consequently, the availability of EBUS equipment has increased exponentially [3]. However, this rapid dissemination has occurred without a consensus on how operators should be trained and how procedural competency should be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…5,22 Although there are fewer data on TBNA and EBUS underuse, surveys of pulmonologists and pulmonary fellows have shown that bronchoscopy training varies signifi cantly, and presumably, practice patterns vary accordingly. 9,10,[23][24][25] This is in the context of randomized strategy of sampling peripheral lung masses fi rst. 17 The present study adds to the existing body of knowledge in this area.…”
Section: Discussionmentioning
confidence: 99%
“…EBUS-TBNA or mediastinoscopy fi rst with thoracotomy to follow if the nodes are normal are both controlled studies demonstrating that EBUS-TBNA is at least as good as mediastinoscopy and, in some cases, is more effective and less costly than mediastinoscopy. [26][27][28] More recent studies suggested that EBUS-TBNA is gaining traction, 25 but how far it has penetrated into the community is not clear. The present study builds on the existing literature in this area by more directly measuring the quality gap.…”
Section: Discussionmentioning
confidence: 99%